TAX PLANNING IN THE ACCOUNTING AREA OF THE COMPANY REPRESENTATIONS NARET S.A.C. - LA MOLINA, 2019 - Vega-Quispe, Lizbeth (2020)
Objective: The objective of the study was to describe tax planning in the accounting area of the company Representaciones NARET S.A.C. - La molina, 2019. Materials and methods: The research is quantitative, its design is nonexperimental, explanatory level. The technique of data collection was observation and the guiding instrument of observation tax planning which is comprised of 15 items grouped in 3 dimensions. Results: In the results it is found that tax planning in the documentation observed and reviewed predominated that has planning with (49%), and the (51%) has no planning. As for the dimensions with IS in taxes (55%), tax obligations (50%), tax infractions (42%). Conclusion: It could also be concluded with respect to tax planning the company does not have adequate planning. Where dimensions show intermediate percentages.